Students' Assertive Behavior Differences Based On from Gender and Parenting Parents and Their Implications in Guidance and Counseling - Resi Anggraini; A. Muri Yusuf; Alwen Bentri (Global Econedu, 2019)
This research is based on the lack of development of assertive behavior of students in school. Students who have good assertive behavior can be seen from the ability of students to make decisions, able to express feelings of honesty and comfort, be able to defend themselves, be able to express opinions, and not ignore the rights of others. Factors that influence students' assertive behavior include gender and parenting parents. Assertive behavior of students in terms of male and female sex and parenting parents will be different, the difference in assertive behavior of students is influenced by several factors both internal factors and external factors. This study aims to describe and distinguish students' assertive behavior in terms of gender and parenting style and its implications in Guidance and Counseling services. The population in this study were all students in SMA N 1 Payung Sekaki Kabupaten Solok. The sampling technique uses stratified random sampling. The instrument used is a Likert scale model. Data analysis using two-way variance analysis (ANAVA) technique.The results of data analysis show that: (1) Assertive behavior of students in terms of gender, namely men and women are in the moderate category, there are significant differences where the average score of men is higher than women, (2) Assertive behavior students in terms of parenting, namely authoritarian, permissive, and authoritative parenting, are in the moderate category, but there are no significant differences, meaning there is no difference in assertive behavior of students in terms of parenting, (3) sex and parenting style in explaining the description of student assertive behavior. The implications of the results of the research for implementing guidance and counseling are as material for consideration of the preparation of BK service programs in developing and enhancing student assertive behavior.